Penerapan HOTS (Higher Order Thinking Skills) dalam Eksplorasi Ide pada Mata Kuliah Kitabah - Yasmar, Renti; Sulaikho, Siti; Munir, Muhammad Syahrul; Asrori, Imam; Machmudah, Umi (Institut Agama Islam Negeri (IAIN) Metro, 2023)
Idea generation, a cognitive process requiring creativity and action, is the focal point of this study. It aims to evaluate the learning needs of PBA students in Maharatul Kitabah, focusing on higher-order thinking skills (HOTS) for idea generation. The study employs educational research and development methods, iteratively aiming to align outcomes with predetermined goals. The learning model development in this study is guided by learning design procedures, emphasizing the Dick and Carey model. This design process entails three stages: (1) initial research, (2) model design, and (3) feasibility testing. The findings reveal a need for more students' Arabic writing skills, necessitating various activities to bolster high-level thinking competencies in the Kitabah course. These activities encompass strategies like tartib al mahdar, tartib al qishshah min shuwar, washf al–shurah, ta'liq al-nash, and tartib al–nash. All these efforts are directed at enhancing students' writing competence.